Anti-inflammatory activity of the epicuticular wax and its isolated compounds catechin and gallocatechin from Eugenia brasiliensis Lam. (Myrtaceae) leaves. Issue 22 (18th November 2021) - Siebert, Diogo Alexandre; Paganelli, Camila Jeriane; Queiroz, Gustavo Silva; Alberton, Michele Debiasi
Abstract: This study describes anti-inflamatory activity of epicuticular wax (ECW) extracted from leaves of Eugenia brasiliensis Lam., and its isolated compounds, catechin and gallocatechin in a pleurisy model in mice. The results for exudation and cell migration showed that the extract and isolated compounds from the plant were effective in inhibiting these inflammatory parameters. The ECW demonstrated a dose-dependent effect on the inhibition of cell migration. The results for NOx levels reveals that the isolated compounds from Eugenia brasiliensis were effective in inhibiting the production of this inflammatory mediator, however, ECW were not able in inhibiting the production of NO in the pleural cavity, at the tested doses. The results here obtained, helps to reinforce the scientifically hypothesis that E. brasiliensis has an important anti-inflammatory activity, and that this effect may be, at least in part, by the presence of the compounds catechin and gallocatechin. Graphical Abstract: